Making Sense of Dignity: A Starting Point - Peonidis, Filimon (Conatus - Journal of Philosophy, 2020)
Although appeals to human dignity became quite popular after the end of War World II in various moral and legal settings, the term retained an air of semantic indeterminacy, and scholars are of opposing minds concerning its usefulness and significance. In this essay I intend to offer a sketch of a “deflationary” account of human dignity – viewed as one moral value among many others – according to which it is conceived as the minimal respect we prima facie owe to our own personality, as well as to the personality of everyone else without any restriction or exception. This account is accompanied by a justification, which does not presuppose the endorsement of a particular moral theory, and envisages dignity as a bulwark to counter the morally abhorrent consequences of many categorical and normatively tainted dichotomies western societies have created.